Melisopalynological potential of chestnut (Castanea sativa Mill.) in Bosnia and Herzegovina (Annals of the Institute of Biology, 2022)
Tame chestnut (Castanea sativa Mill.) is a woody plant species from the family Fagaceae. Chestnut belongs to the group of honey-bearing plants with a high production of pollen and nectar, and honey is characterized by specific chemical and organoleptic properties and a high content of minerals. Its biogeographical distribution is limited to only three areas on the territory of Bosnia and Herzegovina. The aim of the work is to determine the distribution and representation of the pollen of this honey plant in honey samples originating from Bosnia and Herzegovina. For research purposes, 100 honey samples were collected directly from the producer. Based on the micromorphological characteristics of the pollen grains, honey plants, and the exact number of their pollen grains were identified. A total of 4,520 chestnut pollen grains were identified in 40 analyzed melissopalynological profiles of honey. It was concluded, that the specific geographical and ecological distribution of chestnuts in the territory of Bosnia and Herzegovina directly affects the melissopalynological composition of the samples, as well as the botanical characteristics of the honey.